Birth and mortality in Brazil in the period 2018 TO 2021 (Seminário Internacional de Informação, Tecnologia e Inovação, 2023)
After the 2023 census carried out in Brazil, the size of the Brazilian population was taken, the surprise was to find that there was no population growth as we imagined, in this sense this work aimed to analyze, through a survey in the DATASUS database, the birth and death rate in Brazil from 2018 to 2021, inferring about the period of the COVID-19 pandemic, realizing its impacts on the birth and death rate. The result showed that the birth rate was really low, compared to previous periods, another relevant point was the fact that this index points to a decrease in the Brazilian population.
Keywords: Brazil; DATASUS; information; mortality; birth